Challenges in the growth and development of newborns with extra-uterine growth restriction. Issue 5 (3rd September 2022) - Lucaccioni, Laura; Iughetti, Lorenzo; Berardi, Alberto; Predieri, Barbara
ABSTRACT: Introduction: Extra-uterine growth restriction (EUGR) is a condition caused by the failure of very preterm infants to reach their potential growth during the NICU hospital stay. Despite enormous improvements in nutritional support and strategies, the growth pattern of preterm infants is still far from the one expected. Areas covered: This review focuses on what EUGR is, highlighting controversial aspects of this topic. EUGR is still missing a univocal definition, and the international debate is also open on what is the best growth chart to use. Moreover, professionals in NICU may not be trained on how to perform anthropometric measurements, increasing the risk of over- or underestimation, especially for length assessment. EUGR has recently been described as one of the main comorbidities in NICU, influencing growth, metabolism, and neurodevelopment later in life. Expert opinion: There is still much to investigate about what the best growth pattern in the NICU should be. What is known so far is that the majority of preterm neonates develop EUGR, and this leads to several short- and long-term consequences. It is imperative that neonatologists and pediatric endocrinologists work together, to modulate growth in the NICU.